Sistem Informasi Rental Mobil Berbasis Web Menerapkan Unifield Modelling Language - Purnama Sari Tambunan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
CV. Sampagul nauli is one of the businesses engaged in car rental or car rental cv.sampagul nauli transport provides services in the form of car rental types of cars based on price, type and facilities available in each car. In the promotion process the company has done various ways, namely by providing information to each other through one consumer to another, and placing advertisements in newspapers turned out to be less effective because the company could not provide information about the cars being rented completely and in detail so that consumers did not get information that was incomplete and efficient, regarding the cars rented by car rentals so far car rental transactions have been carried out by consumers at the relevant rental, via telephone or coming directly to the rental. Problems also arise in car rentals that take a lot of time because they are still written manually, and rentals via telephone do not satisfy consumers because they cannot see pictures of the cars to be rented, to overcome these obstacles, a web-based car rental information system was built on CV. Sampagul nauli. To make it easier for consumers to rent cars online and see pictures of the cars they want to rent, after we rent or lease a car online, we immediately come to CV. Sampagul to make a transaction again and pick up the car keys. This system uses PHP and MySQL programming languages, and it is hoped that with this web-based car rental information system, it can make it easier for consumers to rent cars, and can produce information that helps companies and consumers